Analisis Penerapan Social Media Marketing Di Lafera Space Pekanbaru (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2025)
This research aims to obtain information and a concrete overview of how the social media marketing strategy is implemented at Lafera Space Pekanbaru. The research method used is descriptive qualitative, which explains descriptively how social media marketing is carried out by Lafera Space. Data collection techniques in this study include interviews with seven informants, documentation studies, literature reviews, and source triangulation. The results of this research show that the coffee shop has successfully implemented the dimensions of content, communication, and collaboration. However, in the connection dimension consumers still experience several challenges that need to be addressed and improved by Lafera Space Pekanbaru.